2019
DOI: 10.1021/acsami.9b04838
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Photodetectors Based on Core–Shell ZnO–Co3O4 Nanowire Heterojunctions

Abstract: Self-powered photodetectors operating in the UV–visible–NIR window made of environmentally friendly, earth abundant, and cheap materials are appealing systems to exploit natural solar radiation without external power sources. In this study, we propose a new p–n junction nanostructure, based on a ZnO–Co3O4 core–shell nanowire (NW) system, with a suitable electronic band structure and improved light absorption, charge transport, and charge collection, to build an efficient UV–visible–NIR p–n heterojunction photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 72 publications
7
53
1
Order By: Relevance
“…Particularly, in the case of p‐on‐n core‐shell nanostructured heterojunction consisting of ZnO nanowires and Co 3 O 4 absorber shell, the fabricated cells resulted in poor PV performance with low V oc (max V oc in the order of tens of mV). [ 34 ] In this respect, while representing the ideal material in terms of E g to boost PCE in all‐oxide solar cells, Co 3 O 4 was the object of very limited studies, and no investigation can be found, in which it is applied as the core of an n‐on‐p inverted structure.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in the case of p‐on‐n core‐shell nanostructured heterojunction consisting of ZnO nanowires and Co 3 O 4 absorber shell, the fabricated cells resulted in poor PV performance with low V oc (max V oc in the order of tens of mV). [ 34 ] In this respect, while representing the ideal material in terms of E g to boost PCE in all‐oxide solar cells, Co 3 O 4 was the object of very limited studies, and no investigation can be found, in which it is applied as the core of an n‐on‐p inverted structure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these radial core–shell heterostructure nanowires can be regarded as “smart materials” with controlled interfaces and enhanced multi-functionalities that can lead to the development of the next-generation high-performance optoelectronic devices 14 16 . Hence, radial core–shell nanowire arrays based on ZnO–Cu x O 16 , ZnO/CuCrO 2 17 , ZnO/WS 2 18 , ZnO–Cu 2 O 19 , ZnO–Co 3 O 4 20 , ZnO/ZnS 21 , CdSe/ZnTe 22 , etc. with applications in photodetectors have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of recently developed self‐powered UV photodetectors (especially photodetectivity) is still unsuitable for practical applications due to energy loss or carrier recombination in the step of light absorption and photogenerated carrier transport. [ 16,17 ] Fabrication of low‐dimensional nanostructures is a promising approach to solve this issue. [ 9,18–20 ] Among different nanostructures, 1D nanoarray structure‐based photodetectors exhibit a series of advantages compared with their thin‐film counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21,22 ] On the one hand, multiple reflection/scattering of incident light in 1D nanoarray materials can significantly increase the probability of light absorption. [ 16 ] On the other hand, 1D nanostructures with minimized charge‐carrier transport paths can reduce the transit time and effectively improve charge carrier separation. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation